Pursuing social justice through public health: gender and sexual diversity activism in Malawi. Issue 1 (2nd January 2017) - Currier, Ashley; McKay, Tara
Abstract : African lesbian, gay, bisexual, transgender, intersex, and queer (LGBTIQ) organizations face various strategic dilemmas in contexts characterized by political hostility to gender and sexual dissidents. In Malawi, we examine how an LGBTIQ social movement organization (SMO), the Centre for the Development of People, navigated one particular strategic dilemma – the dilemma of whether to adopt a less politicized public-health approach or a more nimble, grassroots-oriented, and social-justice approach to their advocacy work. We also examine the consequences of the organization's strategic decisions. Scholars interpret these approaches as signifying differential political engagement among organizations, with the social-justice approach indicating political engagement and the public-health approach signalling political disengagement. This difference has led critics to argue that a public-health approach is poorly suited to generating social and legal reform because it depoliticizes LGBTIQ issues over time, while a social-justice approach exerts constant pressure on political and religious elites. Drawing on qualitative interview data with Malawian LGBTIQ activists and news media data reflecting public debate around homosexuality in the country, we illuminate how this SMO metamorphosed from an organization ostensibly focused only on public health and HIV/AIDS to one that advances social justice for gender and sexual dissidents. We argue for an understanding of the indigenous development of a hybrid strategy integrating the public-health and social-justice approaches.